Family business in the digital age: The state of the art and the impact of change in the estimate of economic value - Olga Ferraro; Elena Cristiano (Journal of Risk and Financial Management, 2021)
Throughout the review of the most relevant literature on family businesses and business valuation, this work pursues a twofold purpose: to explore the possible evolutionary scenarios of family businesses in the era of digitalisation, highlighting their role and purpose; and to determine the valuation approaches that may be applied to them, also in light of the different role that intangible assets deriving from their digitalisation may assume. Therefore, after a description of the most relevant changes related to the digital transformation of the FB, the focus will be set on their valuation, paying special attention to the choice of the most appropriate methodology for 'grasping' the aforementioned changes. Family businesses, in fact, due to their distinctive traits and the various estimation opportunities, require a dynamic business valuation process that has to be projected into the future and suitable for estimating those intangible assets that strongly characterise these types of companies, inasmuch as they are related to the implicit components that are strongly connected to the ownership and are a result of knowledge, strategic adaptability, and product innovation, and their possible impact on the risks and their expected flows. Thus, throughout a systematic literature review, the study provides, on the one hand, a clearer representation of the state of the art of the FB valuation in the digital age; on the other hand, it highlights the characteristics and peculiarities of 'novel' FBs whose valuation needs to be conducted with due care.
Keywords: 330; business valuation; digital era; digital transformation; family business